Repensar a mulher na sociedade: uma prática filosófica que visa a superação da violência contra a mulher a partir do pensamento de Silvia Federici e Bell Hooks - Aguiar, Lhylia Silva (2023)
Having education as an ally in the fight against violence against women, this dissertation aimed to develop philosophical teaching grounded in feminism. The intention of this teaching proposal resulting from the research was to rethink the role of the women in our society, from the analysis of the work that has been socially attributed to women, more specifically on domestic and care work, invisibilized and undervalued thanks to capitalism, making it evident how women are exploited and oppressed. The feminist philosophical thought that underpinned the writing of this dissertation takes into account the historical-dialectical materialist method, used for the analysis of data on violence against women, resulting from the structure that sustains and perpetuates violence. Feminist philosophers’ analyses are presented on how the capitalist patriarchal system exploits and oppresses women, underpinning the violence that affects and victimizes them. The feminist theory that guided the research served as the basis for the proposal of philosophical teaching, with a view to raising students’ awareness. The steps of the teaching proposal included the students’ observation of domestic work carried out within their homes. From the perceptions elements were raised for the second moment, which concerns the analyzes carried out by the feminist Silvia Federici about the reproductive work (domestic services and care). This material was used to reflect on exploitation and violence against women. The thought of bell hooks was used as guidance for a research undertaken by the students, in which they related the feminist movement to the conquest of the rights acquired by women. Both the research and the teachings served for them to write their perceptions about the learning process in the course of the teaching proposal.